Pengadilan Tata Usaha Negara (PTUN) Sebagai Media Pengawasan Masyarakat Untuk Mewujudkan Pemerintahan yang Bersih dan Berwibawa - Erna Susanti (Fakultas Hukum Universitas Mulawarman, 2009)
The administrative court is established to settle the dispute between the government and its citizen. The dispute arises from a governmental act which is considered breaching citizen rights. It could be concluded that the administrative court principally is established to protect the citizen. In other terms, the purpose of administrative court actually not only to preserve the individual rights, but also to protect public rights and to be a media for the community to control any policies which are issues by the government in order to achieve good governance